2017
DOI: 10.1155/2017/1864321
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Tuning Proportional‐Integral‐Derivative‐Based Temperature Control Method for Draw‐Texturing‐Yarn Machine

Abstract: Owing to the fast time-varying characteristics, the temperature control for draw-texturing-yarn (DTY) machine has higher technical difficulties and results in challenges for system energy optimization. To address the matter, a self-tuning proportionalintegral-derivative-(ST-PID-) based temperature control method is proposed. Referring to the technical procedures of DTY machine, a thermodynamic model is set up. Then, a ST-PID minimum phase control system is constructed by the pole-point placement method. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Related researches [44][45][46] suggested that the ultrasonic excitation can increase the internal kinetic energy of the fluid medium, and the turbulence intensity will be enhanced. Moreover, ultrasonic can make fluid create remarkable physical variation, that is, the cavitation phenomenon, which can effectively accelerate the motion states of the abrasive particles.…”
Section: Introductionmentioning
confidence: 99%
“…Related researches [44][45][46] suggested that the ultrasonic excitation can increase the internal kinetic energy of the fluid medium, and the turbulence intensity will be enhanced. Moreover, ultrasonic can make fluid create remarkable physical variation, that is, the cavitation phenomenon, which can effectively accelerate the motion states of the abrasive particles.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the target objects (horse, donkey, mule, and goat) described in Section 4.1, the target image data are acquired by computer vision technology, and the original images are preprocessed by graying and vectorization. Then, the region segmentation for preprocessing images is performed on the selected feature image region [57][58][59][60][61]. In this case, the selected region of the feature image is the head, and the feature region profiles are shown in Figure 8.…”
Section: Instance Design Of the Cognitionmentioning
confidence: 99%
“…According to micro-cutting wear mechanism [46][47][48], a small part of the abrasive particle is pressed into the machining surface by the normal force. Then, an abrasive particle is driven by the friction between the base fluid and abrasive particle.…”
Section: Normal Grinding Force Of Abrasive Particlementioning
confidence: 99%